2017
DOI: 10.1002/2016jg003708
|View full text |Cite
|
Sign up to set email alerts
|

Autoxidation as a major player in the fate of terrestrial particulate organic matter in seawater

Abstract: The Rhône River plays a major role in the Mediterranean Sea, being both its main freshwater source and its major particulate matter provider. This survey of the fate of terrestrial particulate organic matter (POM) was conducted along the salinity gradient of the Rhône River plume, between 2012 and 2014. It revealed that autoxidation acts rapidly and intensely upon the POM's arrival at sea, with α‐amyrin and β‐amyrin autoxidation rates going from 12.9 ± 2.9% to 45.0 ± 6.4% and 10.7 ± 4.0% to 50.3 ± 4.4%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 65 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…Cleavage was attributed to some redox-active metal ions released from suspended particulate matter (SPM) in the mixing zone of riverine water and marine water. Using new lipid tracers specific to the degradation of terrestrial higher plants at the mouth of the Rhône River (Galeron et al, 2016a,b;Rontani et al, 2015), we confirmed the role played by autoxidation in the degradation of terrestrial POM (TPOM) in estuaries (Galeron et al, 2017). As in the Beaufort Sea (Rontani et al, 2014a), autoxidation rate and salinity level appeared to correlate well within the river plume in the Mediterranean Sea (Galeron et al, 2017).…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…Cleavage was attributed to some redox-active metal ions released from suspended particulate matter (SPM) in the mixing zone of riverine water and marine water. Using new lipid tracers specific to the degradation of terrestrial higher plants at the mouth of the Rhône River (Galeron et al, 2016a,b;Rontani et al, 2015), we confirmed the role played by autoxidation in the degradation of terrestrial POM (TPOM) in estuaries (Galeron et al, 2017). As in the Beaufort Sea (Rontani et al, 2014a), autoxidation rate and salinity level appeared to correlate well within the river plume in the Mediterranean Sea (Galeron et al, 2017).…”
Section: Introductionsupporting
confidence: 67%
“…1). Sampling and hydrographic conditions have been described by Galeron et al (2017). High frequency monitoring of the nutrients and of the PM input from the Rhône to the Mediterranean has been carried out since 2010 in the framework of the national program MOOSE (Mediterranean Ocean Observing System for the Environment).…”
Section: Sampling Of Spm and Sediments From The Rhône Mackenzie And mentioning
confidence: 99%
See 2 more Smart Citations
“…The low autoxidation percentages of amyrins measured in the samples investigated (Table ) give good support to these previous observations. Interestingly, the autoxidation percentages (Table ) also appeared to be considerably lower in the Têt River than in the closer Rhône River . These differences were attributed to the size of the particles analysed (>63 μm in the Têt River and > 0.7 μm in the Rhône River).…”
Section: Resultsmentioning
confidence: 90%